2017
DOI: 10.18632/oncotarget.16770
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of the time of repeated computed tomography and replanning for patients with nasopharyngeal carcinoma

Abstract: PurposeTo study the necessity of repeat computed tomography (CT) scan and replanning and know a more accurate time using weekly kilovoltage cone beam computed tomography (kV-CBCT) scans for patients with nasopharyngeal carcinoma (NPC) during radiotherapy.Methods and MaterialsThirteen NPC patients treated with IMRT were enrolled into this prospective study. Weekly pretreatment kV-CBCT scans were performed on the 1st, 6th, 11st, 16th, 21st and 26th radiation time, respectively. Target delineations were contoured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…22 Although this present study did not assess the gland size during radiotherapy, such shrinkage was started around the middle and late stage of the treatment course according to previous studies. 28,29 Fung et al 30 reported that parotid glands shrank at a mean rate of 1.35% per day and demonstrated an average medial migration of 0.34 cm after a course IMRT in NPC patients. Since changes in location and size during radiotherapy course would lead to increase dose to the salivary glands, adaptive radiotherapy with re-planning around mid-and/or late course of treatment were suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Although this present study did not assess the gland size during radiotherapy, such shrinkage was started around the middle and late stage of the treatment course according to previous studies. 28,29 Fung et al 30 reported that parotid glands shrank at a mean rate of 1.35% per day and demonstrated an average medial migration of 0.34 cm after a course IMRT in NPC patients. Since changes in location and size during radiotherapy course would lead to increase dose to the salivary glands, adaptive radiotherapy with re-planning around mid-and/or late course of treatment were suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Since changes in location and size during radiotherapy course would lead to increase dose to the salivary glands, adaptive radiotherapy with re-planning around mid-and/or late course of treatment were suggested. 28,29,31,32 Salivary glands have been demonstrated to show recovery after the completion of radiotherapy. 33,34 Van Luijk et al suggested that the stem or progenitor cells in the human parotid gland, which provided the regenerative capacity of the gland tissue in the irradiated region, were responsible for the recovery of parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Growing reports have demonstrated there is no direct dose-effect relationship between the parotid dose and xerostomia for NPC patients [28,29]. The reasons might be that the parotid dose revealed in the pre-treatment plan was different from the actual dose received because of the positional change of the gland during the treatment process and the mean dose of parotid in most NPC patients beyond the dose constraints recommended from the QUANTEC guideline [30,31]. In contrast, GTV was observed to be predictive of xerostomia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) has a distinct advantage of high conformity and is an appropriate technique for treating nasopharyngeal carcinoma (NPC). Previous studies have demonstrated that anatomical changes in the external contour, shape, and location of the target and critical structures are significant and result in dosimetric changes [1, 2]. Patients’ quality of life and clinical outcomes might be improved by IMRT replanning [3].…”
mentioning
confidence: 99%
“…On the basis of results of previous studies [1, 2], we chose to perform a second CT simulation (CT-II) after the 22nd fraction of radiotherapy, leaving 3 days for radiophysicists to make plan-II. For the first 11 patients, considering the inadequate time for determining adaptive plans, we implemented the plan-II radiotherapy after the 26th fraction.…”
mentioning
confidence: 99%